Hey there! :D
So, we know that there are 3 z's and 3 6's.
3*z= 3z
6*3= 18
3(z+6) <== equivalent expression
3z+18 <== equivalent expression
z is by itself. It shouldn't combine. It should stay the same. 6 as a unit is separate from z.
Choices "B" and "E" are correct.
I hope this helps!
~kaikers
Answer:
EK = 9
Step-by-step explanation:
x + 11 = -5 + 2x -5 + 2x
x+11 = -10 + 4x
11 = 3x - 10
3x = 21
x = 7
EK =-5 + 2 × 7
EK = 14 - 5
EK = 9
-1 i think that the answer is -1
I know the answers but I hate simplifying
40) 9y-12
42) -3x+3y-5
I’m not to sure I was wondering the same thing